Extraction and characterization of pepsin enzyme from the skipjack vicera (Katsuwonus pelamis) - Muttaqin Roisul Adi Brilianto; Surya Amalia; Istiarini Istiarini; Duanassurya Megana; Samosir Wisda; Makatita Suciarti; Nurhayati Tati (BIO Web of Conferences)
Pepsin is one of the digestive enzymes often used in various fields, especially for industry. Pepsin can be extracted from fish viceras. The aim of this research is to extract pepsin from the stomach of skipjack tuna, purify it, and to characterize several biochemical properties of the pepsin produced. The samples used were skipjack tuna stomachs extracted by adding tris-HCl buffer pH 7.5, centrifuged, and activated. The pepsin crude extract was then characterized by temperature, pH and optimum pepsin substrate. The crude pepsin extract of skipjack tuna showed the best activity in the range temperature 50 °C with a pH of 3. Pepsin purification is carried out using ammonium sulphate with a range of 30-80%. The band produced in each pepsin purification pellet sample is estimated to be between 31-32 kDa, while in the supernatant a thin band remains which indicates that all the proteins in the supernatant have been degraded by ammonium sulphate.